2017
DOI: 10.7322/jhgd.127647
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the nutritional status in children aged 5 to 10 years old on the Conditional Cash Transfer Programme in the States of Acre and Rio Grande do Sul, Brazil

Abstract: Introduction: In recent years, there has been a reduction in cases of malnutrition in Brazil but this has been accompanied with an increase in the overweight and obesity rates. These changes, together with others, such as changes in eating patterns and lifestyle, characterise the process of nutritional transition. Objective: We aimed to compare the prevalence of nutritional status of beneficiary children of the Bolsa Família Program (PBF) in the states of Acre and Rio Grande do Sul, Brazil, and to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Discussing and proposing solutions to reduce traffic violence is a relevant and current fact in the field of public health. In addition, it has already been identified that effective Public Health programs contribute to the reduction of mortality from specific causes, favoring the reduction of noncommunicable diseases at all ages, including among children and adolescents [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Discussing and proposing solutions to reduce traffic violence is a relevant and current fact in the field of public health. In addition, it has already been identified that effective Public Health programs contribute to the reduction of mortality from specific causes, favoring the reduction of noncommunicable diseases at all ages, including among children and adolescents [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue of JHGD these studies evaluate technologies that involve the improvement of health conditions and/or issues for public health investigating the health situation of the population, especially children and adolescents [8][9][10] , which corroborate the themes in the health promotion field within the context of primary care focusing on teens and their vulnerabilities [11][12][13] , nutrition and influence on child and adolescent development [14][15][16][17][18] and themes focused on translational medicine, describing results to improve the health indicators of the population [19][20][21][22] . With an emphasis on nutritional status, to highlight obesity in adolescents, Tebar et al 17 found the prevalence of abdominal obesity in adolescents in the city of Londrina, Paraná, Brazil, and its associated factors.…”
mentioning
confidence: 81%
“…In a literature review, only three studies were identified with SISVAN data or on the anthropometric profile of children in the Northern region of Brazil [6][7][8]. The state of Rondônia has a population composed of immigrants from all regions of the country who came to Rondônia mainly in the 1970s to occupy the land, in addition to local people such as indigenous and riverbank dwellers, thus making the Rondônia population one of the most diverse in Brazil.…”
Section: Introductionmentioning
confidence: 99%